Cross gramian based time interval model reduction - Haja Mohideen, Ahmad Jazlan; Sreeram, Victor; Togneri, Roberto (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents the development of new Sylvester equations for both continuous and discrete time linear SISO and symmetric MIMO systems in order to obtain the time interval cross gramian matrices which have time interval controllability and observability information contained in a single matrix. Numerical examples are provided to demonstrate the computational efficiency of the proposed method which requires computing only the time interval cross gramian compared to existing techniques which require the computation of both time interval controllability and observability gramians simultaneously.